Leukemic children: clinical and histopathological gingival lesions - (:unkn) unknown (My University, 1998)
The relation between leukemia and gingiva was investigated in the present study. An extensive tumor infiltration in the gingiva was established in 1 of 2 patients with acute leukemia (AML). An inflammatory cell infiltration in various degrees was noticed in total 28 patients with leukemia (L). Various degrees of epithelium hyperplasia in all patients existing in 14 patients with medium intensity and occurring in 14 patients with light intensity of hyperplasia were observed. An increase in the keratinization of epithelium, in 3 patients with medium intensity and 1 patient with light intensity was found. It was also seen that there were fungal infections in 3 patients with medium intensity, in 6 patients with light intensity and existing in a total 26 patients with acute lymphoblastic leukemia (ALL).
Keywords: Humans; Gingival Diseases; Adolescent; Gingiva; Child; Dental Caries; Case-Control Studies; Hydrogen-Ion Concentration; Saliva; Dental Care for Chronically Ill; Secretory Rate; Leukemic Infiltration; Epithelium; Hyperplasia; Mycoses; Precursor Cell Lymphoblastic Leukemia-Lymphoma